Anti-inflamatory response of poultry challenged with LPS of Escherichia coli (Research, Society and Development, 2020)
To evaluate the anti-inflammatory response of poultry, body weight (BW), body weight loss (BWL), cloacal temperature (CT) and expression of interleukin-10 (IL-10) after LPS application were calculated. A total of 19-day-old male broilers were used. At 17 days, the broilers were weighed and distributed in 12 metal cages with 1 animal per experimental unit. Intraperitoneal application of LPS was realized through 1 ml/kg of body weight at 19 days of age at time zero. For each treatment, that is, each time after the application of the LPS, the temperature of the poultry was measured. Afterwards, this chicken was weighed to determine body weight and body weight loss. Finally, the broiler was euthanized by cervical dislocation and collected their spleens for analysis of IL-10 mRNA expression. The analysis of the results obtained during the performance of this work concludes that the application of LPS of Escherichia coli directly interferes in the body weight loss of the animals (Y = - 0.09617 - 1.54780 x + 0.19107 x2) in 3.2307 % after 4.05 hours of application, and which directly interferes with the Gene Expression of the Interleukin-10 (Y = 1.33367 + 3.23013 x - 0.31733 x2), having its peak of expession after 5,0895 hours of application with a concentration of 9,53364 A.U..